Libertação, conversão e catequese em Jo 9. Estudo do texto, suas consequências na comunidade joanina e indicativos para catequese - Togneri, Silvia Regina Nunes da Rosa (2011)
Liberation, Conversion and Catechesis have the purpose, in John 9, to identify the itinerary of a person born blind in order to profess publicly his adhesion of faith to Jesus, as the Son of Man, in a time of exclusion from the synagogue. The liberation from laws and rules not directed towards defending life and, therefore, not according to the will of God, with regard to an excluding situation, takes courage after having opened eyes and mind. The first chapter considers the gospel according to the community of John as a whole, pointing out its main characteristics, its relation to the Jewish Feasts and the Sabbath. Chapter two deepens the study of the narration about the healing of the man born blind so as to make clear how liberation, conversion and catechesis become evident in the text. The narration presents the process of adhesion to Jesus as the Son of Man, showing how, accordingly, Jesus has to be seen exactly like he is. Therefore, the person who professes faith in Him, even in times of punishment and exclusion by the Jews and Pharisees, needs having his eyes gradually opened. The understanding of who Jesus is begins with doing what he orders, confronting courageously the questionning by the group of Jews Pharisees and not fearing to express an opinion contrary to theirs, even at the risk of punishment. The man born blind now healed, who lets himself be illuminated by Jesus, is a model for the community. Chapter three shows how the text of John 9 can be used for catechesis and how the community of John, the Jewish and the ancient Christian communities developed their catechetical process. Based on the itinerary of liberation and conversion made by the man born blind now healed, indicative elements for the catechesis of adults in our days are presented.